Analysis of The Management of The Village Revenue and Expenditure Budget in Pejaten Village Serang Regency 2024 - Siti Rukoyah; Amanda Ayu Kholidjah Siregar (Universitas Sultan Ageng Tirtayasa, 2026)
The management of the Village Revenue and Expenditure Budget (APBDes) is a crucial aspect in supporting village governance, development implementation, and the improvement of community welfare. Although it is governed by various regulations, the implementation of village financial management still faces a number of challenges that can affect the effectiveness and accountability of budget utilization. This study aims to examine the implementation of APBDes management for the 2024 Fiscal Year in Pejaten Village, Serang Regency. The study employs a descriptive qualitative approach using data collection techniques such as interviews and documentation. Information was obtained from village officials involved in financial management and supported by various administrative documents and village financial reports. The research results indicate that the APBDes management process from planning, implementation, record-keeping, reporting, to accountability has been carried out in accordance with applicable regulations. However, its implementation is still affected by several constraints, including limited staff competence, delays in the disbursement of Village Funds, administrative obstacles, technical disruptions in the Siskeudes system, and insufficient transparency of budget information to the public. Therefore, efforts are needed to strengthen staff capacity, enhance transparency, and optimize village financial management to support sustainable and accountable village development.